Terra incognita of vitality problem: Open issues. Part 1 - Vladimir A. Tolochek (Saratov State University, 2021)
The increase of uncertainty, instability, complexity, ambiguity of the dynamics of the condition of social subjects are among the issues that make vitality problem topical. This results in higher standards for adaptation mechanisms of an individual and social groups (families, work groups, sports, management, project teams) and greater importance of socio-psychological and psychological resources of a person. Not all spontaneously formed adaptation mechanisms of individual and group subjects are adequate for real-life situations, not all of them are developed when it is neces-sary and change when the goals and requirements of the environment change. The purpose of the study is to conduct research of human vitality under uncertainty conditions; the object of the study is: social and psychological mechanisms and human vitality resources; methods include: historical and theoretical analysis, analysis of empirical research results. Hypothesis: The first stage is maintaining the vitality of an individual and social groups via formation of prosocial mechanisms of behavior according to a model (prototype). The following development stages of vitality involve forming adapta-tion mechanisms initiated and supported by the evolution of the "internal conditions" of the subject. We analysed the materials related to vitality study in foreign and domestic psychology from the 1960s to the present: historically emerging approaches (five "waves"), subject and tasks, mechanisms and types of human adaptation to the physical and social environment. It is stated that, within the boundar ies of historically formed paradigms, two human states are considered - "below the norm" and "norms" of social, psychological, physical functioning, characteristics of which are described by the concepts of "improvement", "positive adaptation", "preservation", "back to normal", "optimal condition", "achieving a good result"; vitality is viewed as the achievement and maintenance of "social homeostasis" by a person, with the focus on the prosocial behavior models of other people, who are reproducing such models. Climbing the heights of physical and spiritual maturity, reaching a higher level of social functioning, the effects of positive changes in survivors of traumatic events remain unexplored, and retain the status of terra incognita.